PENINGKATAN KAPABILITAS DIGITAL MARKETING: UPAYA KELOMPOK TANI MEMPERLUAS PASAR GLOBAL - Santi, Fitriana; Tsamroh, Dewi ‘Izzatus; Yazirin, Cepi; Setyawan, Pungky Eka; Fadillah, Rahmad Fahil; Anitasari, Silvi (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRACTMarketing is one of the main factors in the development of both goods and services. The village group of Bunton Village is a group of individuals who have the same goal of being profit-oriented. The presence of an average peasant group consisting of individuals of underage age makes the minimum knowledge of the use of digital technology as a media of promotion. While rice as a product is ultimately a daily necessity that cannot be stopped in the country of Indonesia. Aware of this, the service team provides training on the use of social media as a means of implementing digital marketing. It is undeniable that creating content in the 4.0 era helped the effort to reach global market share coverage. The service team provided training on how to create simple content to attract global market interest. The socialization activity was attended by 15 members of the village village group Bunton, and the event was held on September 30, 2023, at the home of the head of the village village group Buntons, called Wagir. The benefits of using social media as a means of providing information about a product will ultimately increase the revenue receipt of the Bunton Village Tani groupKeywords: digital marketing, expansion, global market, trainingÂ ABSTRAKPemasaran adalah salah satu jantung utama dalam perkembangan usaha baik barang maupun jasa. Kelompok tani Desa Bunton adalah Kumpulan individu yang memiliki tujuan sama yakni profit oriented. Kehadiran kelompok tani yang rata-ratga beranggotakan individu dengan usia yang tidak belia lagi membuat minimnya pengetahuan akan pemanfaatan teknologi digital sebagai media promosi. Padahal beras sebagai produk akhirnya merupakan kebutuhan sehari-hari yang tidak mungkin berhenti di negara Indonesia. Menyadari akan hal tersebut maka tim pengabdi memberikan pelatihan penggunaan media sosial sebagai sarana implementasi dari digital marketing. Tidak dapat dipungkiri bahwa membuat konten di era 4.0 membantu usaha mencapai cakupan pangsa pasar global. Tim pengabdi memberikan pelatihan cara membuat konten sederhana untuk dapat menarik minat pasar global. Kegiatan sosialisasi dihadiri 15 anggota kelompok tani Desa Bunton dan acara dilakukan pada tanggal 30 September 2023 di rumah ketua kelompok tani Desa Bunton Kecamatan wagir. Hasil kegiatan menunjukkan minat anggota untuk membuat konten dan upload di media sosial. Manfaat penggunaan media sosial sebagai sarana penyampaian informasi akan sebuah produk pada akhirnya dapat meningkatkan penerimaan pendapatan kelompok Tani desa Bunton.Kata Kunci: digital marketing, pasar global, pelatihan, perluasan